Parenting : an ecological perspective - Luster, Tom; Okagaki, Lynn (Monographs in parenting series., 2005)
Parenting: An Ecological Perspective was originally created in 1993. Luster and Okigaki have updated the original text focusing on parental behavior and also included new chapters covering topics such as: Fathers/gender of parent; Children with special needs; Ethnicity and socioeconomic status; and Parent education.